Profile of Skin Tumors at Dr. Zainoel Abidin General Hospital Dermatology and Venerology Outpatient Clinic in 2017 – 2021 : A Retrospective Study - Wahyu Lestari; Nanda Earlia Fitria; Sitti Hajar; Mimi Maulida (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Skin tumors are swellings caused by proliferation or failure of cell death mechanisms. Based on the type of growth, skin tumors are divided into benign tumors and malignant tumors. Purpose: To investigate the incidence of skin tumors in Dr. Zainoel Abidin General Hospital outpatient clinic. Methods: This study is a descriptive study with total sampling. The diagnosis of skin tumors is assessed based on medical records filled by Dr. Zainoel Abidin General Hospital Dermatovenerologist in January 2017-September 2021. Result: The results showed patients diagnosed with benign skin tumors had as many as 360 subjects and malignant tumors had as many as 4 samples. The majority of women are affected by benign and malignant skin tumors. Based on the age of benign tumors dominated by the age of 22-45 years while in malignant tumors dominated by 45-64 years. The majority of the sample comes from Banda Aceh, based on where the most of them reside. Based on the size of lesions, benign tumors are dominated by lesions that are less than 0.5 cm in size, while malignant tumors are dominated by lesions that are larger than 0.5 cm in size. Based on the presence and absence of recursion the entire dominant sample has no recursion. Based on the physical treatment in benign tumors are dominated by electrocautery action while malignant tumors are the same number between general surgery and FNAB. Conclusion: most of the skin tumors found in Dr. Zainoel Abidin General Hospital dermatology and venerology outpatient clinic are benign